Nondestructive Evaluation of FRP-Concrete Interface Bond due to Surface Defects - Nur Yazdani; Eyosias Beneberu; Mina Riad (Advances in Civil Engineering)
Carbon fiber-reinforced polymer (CFRP) laminates have been successfully used as externally bonded reinforcements for retrofitting, strengthening, and confinement of concrete structures. The adequacy of the CFRP-concrete bonding largely depends on the bond quality and integrity. The bond quality may be compromised during the CFRP installation process due to various factors. In this study, the effect of four such construction-related factors was assessed through nondestructive evaluation (NDE) methods, and quantification of the levels of CFRP debonding was achieved. The factors were surface cleanliness, surface wetness, upward vs. downward application, and surface voids. A common unidirectional CFRP was applied to small-scale concrete samples with factorial combinations. Ground-penetrating radar and thermography NDE methods were applied to detect possible disbonds at CFRP-concrete interfaces. Thermography was found to clearly detect all four factors, while the GPR was only effective for detecting the surface voids only. The thermal images overpredicted the amount of debonded CFRP areas by about 25%, possibly due to scaling errors between the thermograph and the sample surface. The maximum debonded CFRP area in any sample was about two percent of the total CFRP area. This is a negligible amount of debonding, showing that the factors considered are unlikely to significantly affect the laminate performance or any CFRP contribution to the concrete member strength or confinement.